Comparative analyses of caste, sex, and developmental stage‐specific transcriptomes in two Temnothorax ants. Issue 10 (30th March 2020) - Gstöttl, Claudia; Stoldt, Marah; Jongepier, Evelien; Bornberg‐Bauer, Erich; Feldmeyer, Barbara; Heinze, Jürgen; Foitzik, Susanne
Abstract: Social insects dominate arthropod communities worldwide due to cooperation and division of labor in their societies. This, however, makes them vulnerable to exploitation by social parasites, such as slave‐making ants. Slave‐making ant workers pillage brood from neighboring nests of related host ant species. After emergence, host workers take over all nonreproductive colony tasks, whereas slavemakers have lost the ability to care for themselves and their offspring. Here, we compared transcriptomes of different developmental stages (larvae, pupae, and adults), castes (queens and workers), and sexes of two related ant species, the slavemaker Temnothorax americanus and its host Temnothorax longispinosus. Our aim was to investigate commonalities and differences in group‐specific transcriptomes, whereupon across‐species differences possibly can be explained by their divergent lifestyles. Larvae and pupae showed the highest similarity between the two species and upregulated genes with enriched functions of translation and chitin metabolism, respectively. Workers commonly upregulated oxidation‐reduction genes, possibly indicative of their active lifestyle. Host workers, but not workers of the slavemaker, upregulated a "social behavior" gene. In slavemaker queens and workers, genes associated with the regulation of transposable elements were upregulated. Queens of both species showed transcriptomic signals of anti‐aging mechanisms, with hosts upregulating various DNA repair pathways and slavemaker queens investing in trehalose metabolism. The transcriptomes of males showed enriched functions for quite general terms realized in different genes and pathways in each species. In summary, the strong interspecific commonalities in larvae, pupae, and workers were reflected in the same enriched Gene Ontology (GO) terms. Less commonalities occurred in the transcriptomes of queens and males, which apparently utilize different pathways to achieve a long life and sperm production, respectively. We found that all analyzed groups in this study show characteristic GO terms, with similar patterns in both species. Abstract : The aim of the present study is to identify characteristic gene expression patterns of ant larvae, worker pupae, workers, queens, and males. The study uncovers commonalities and differences within and between the two ant species Temnothorax americanus and Temnothorax longispinosus —a parasitic slave‐making ant species and its host.